2013
DOI: 10.5194/gi-2-275-2013
|View full text |Cite
|
Sign up to set email alerts
|

Automated field detection of rock fracturing, microclimate, and diurnal rock temperature and strain fields

Abstract: Abstract. The rates and processes that lead to non-tectonic rock fracture on Earth's surface are widely debated but poorly understood. Few, if any, studies have made the direct observations of rock fracturing under natural conditions that are necessary to directly address this problem. An instrumentation design that enables concurrent high spatial and temporal monitoring resolution of (1) diurnal environmental conditions of a natural boulder and its surroundings in addition to (2) the fracturing of that boulde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Warren et al . () also observed that cracking was typically coincident with short‐term temperature cycling driven by weather such as wind or cloud‐cover. Such short‐term temperature cycling has been observed in a range of climates (e.g.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Warren et al . () also observed that cracking was typically coincident with short‐term temperature cycling driven by weather such as wind or cloud‐cover. Such short‐term temperature cycling has been observed in a range of climates (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, calculated times of peak solar‐induced rock scale (Shi, ) and grain‐to‐grain (Eppes et al ., ) stresses coincide with peaks in the magnitude of observed cracking, as measured by acoustic emissions in boulders placed in humid temperate sites within 20 km of the NC Forested site (Eppes et al ., ; Warren et al ., ). Warren et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The active influence of the diurnal directional solar weathering has also been proved by acoustic emission records in natural field conditions. Measurements performed by Warren et al () on a small (25 cm) granite boulder showed that acoustic emission events associated with rock cracking occur indeed in relation to the diurnal cooling of the rock surface (at around 6:00 p.m. in the study settings) and also in relation to STCs associated with wind intensification, cloudiness and rain, as previously assumed based on thermal records (Hall and André, ; Gómez‐Heras et al , ). Compared to the continuous daily insolation, STCs related to summer rain occurrence (which we consider highly active in the study area) are thought to impact the rock dissimilarly, i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Both short‐term temperature changes (STCs) and diurnal thermal stress induced by solar action have been emphasized as inducing permanent mechanical damage in rocks and triggering thermal weathering in various humidity conditions, their occurrence and efficiency being discussed in different climatic environments (Hall, ; Guglielmin et al , ; Hall et al , ; Viles, ; McKay et al , ; Molaro and McKay, ). Grain and crystal‐size temperature studies (Hall and André, , ; Gómez‐Heras et al , ) are available to prove the existence of significant mineral expansion and damages produced in polymineral rocks consequent to natural thermal oscillations even at mid‐latitudes (Gómez‐Heras et al , ), and unequivocal proofs of rock damage occurrence have been recently provided to sustain the effective action of diurnal directional isolation stress (Warren et al , ) or freeze–thaw action upon rock surfaces (Sass, ; Amitrano et al , ; Girard et al , ; Duca et al , ).…”
Section: Introductionmentioning
confidence: 99%